Analisis Pola Kalimat Dalam Tulisan Mahasiswa Bipa Fakultas Sastra Dan Budaya, Universitas Udayana - Inelda Nivirawati, Revina; Suparwa, I Nyoman; Teguh, I Wayan (Humanis, 2016)
This study entitled "Analysis of Sentence Patterns in Student Writing BIPA Faculty of Arts and Culture, University of Udayana. There are three issues that were analyzed in this study, the type of sentence patterns, the type of sentence errors, and obstacles to learning in BIPA Unud sentence. The goal of this research to identify sentence patterns used in writing Unud BIPA student, the type of sentence errors, and constraints in learning Indonesian sentences in BIPA Unud. Data collection methods used in this study, the method see and interviews with technical notes, then the data were analyzed using methods agih with basic techniques. The next presentation of the results of data analysis used formal and informal methods. Source of data used are written in a writing lesson, the student essay BIPA and BIPA interview to the students of the Faculty of Literature and Culture, University of Udayana 2014¬¬ the period September-January 2015. The theory used is a psycholinguistic theory, the theory of raw monitor and grammar language Indonesia, which is the sentence. In the present study found a variety of sentence patterns, which includes a single sentence patterns and pattern compound sentences. In addition, also found some errors sentences include improper use of capital letters, spelling errors, spelling errors uptake and use of punctuation errors. In addition, it is known that the BIPA students of the Faculty of Literature & Culture, University of Udayana experienced problems in learning Indonesian, the constraints in terms of language and non language.